Performance of Network-Coding in Multi-Rate Wireless Environments for Multicast Applications - VIERA, Luiz F. M. (Institutional Knowledge at Singapore Management University, 2007)
This paper investigates the interaction between net-work coding and link-layer transmission rate diversity in multi-hop wireless networks. By appropriately mixing data packets at intermediate nodes, network coding allows a single multicast flow to achieve higher throughput to a set of receivers. Broadcast applications can also exploit link-layer rate diversity, whereby individual nodes can transmit at faster rates at the expense of corresponding smaller coverage area. We first demonstrate how combining rate-diversity with network coding can provide a larger capacity for data dissemination of a single multicast flow, and how consideration of rate diversity is critical for maximizing system throughput. We also study the impact of both network coding and rate diversity on the dissemination latency for a class of quasi real-time applications, where the freshness of disseminated data is important. Our results provide evidence that network coding may lead to a latency-vs-throughput tradeoff in wireless environments, and that it is thus necessary to adapt the degree of network coding to ensure conformance to both throughput and latency objectives.